Sarcoidosis as a risk factor for venous thromboembolism - Geremek, Anna Goljan (Sarcoidosis Vasc Diffuse Lung Dis, 2017)
Sarcoidosis as a chronic condition of immune dysregulation might be associated with increased risk of venous thromboembolism (VTE). In this study we report three cases of sarcoidosis and pulmonary embolism (PE) occurring together, that share common clinical, serological and pathological findings, confirming the diagnosis of active pulmonary sarcoidosis and no others co-existing prothrombotic factors. We hypothesized that the hypercoagulability and increased risk for VTE in sarcoidosis may be attributable to active local and generalized inflammatory process. The possible relation of clinical picture of sarcoidosis that favors thrombus formation and the bidirectional inflammation and coagulation process are discussed. Further investigation of PE in patients with sarcoidosis are required as the co-incidence of both diseases seems to be more frequent than expected. (Sarcoidosis Vasc Diffuse Lung Dis 2017; 34: 170-178)